The imprint of labor markets on entrepreneurial performance - Kwon, Seok-Woo; Ruef, Martin (Journal of Business Venturing, 2017)
Using the 1979–2010 waves of the National Longitudinal Survey of Youth, our study tracks the earnings of individual entrepreneurs from the beginning of their entrepreneurial careers, examining the effects of labor markets on their earnings trajectory. Results show that apart from self-selection, labor markets impose a penalty on the initial earnings of entrepreneurs who start a business in adverse economic conditions, a disadvantage that persists for up to a decade. We also identify two factors expected to alleviate the imprinting effect of labor markets: migration outside the imprinting environment and serial entrepreneurship.